Posttraumatic Stress and Posttraumatic Growth in Three Generations of Czech and Slovak Holocaust Survivors - Preiss, Marek; Šamánková, Dita; Štipl, Jiří; Fňašková, Monika; Nečasová, Markéta; Bob, Petr; Heissler, Radek; Prokopová, Alice; Heřmánková, Tereza; Juričková, Veronika; Sanders, Edel; Wagenknechtová, Eva; et al. (Journal of traumatic stress, 2022)
The psychological consequences of trauma related to the Holocaust have been primarily studied in samples derived from Israel, North America, and Western Europe. Few studies have examined postcommunist countries in Central and Eastern Europe. The present study focused on three generations living in the Czech Republic and Slovakia after World War II (WWII): Holocaust survivors (71-95 years of age), their children (30-73 years of age), and their grandchildren (15-48 years of age). We compared scores on measures of posttraumatic stress symptoms (PTSS; the Posttraumatic Stress Disorder Checklist-Civilian Version) and posttraumatic growth (PTG; the Posttraumatic Growth Inventory) derived from three focal samples with scores from age-matched comparison participants. Higher PTSS scores emerged for Holocaust survivors in all generations, η2 P=.087 but only participants in the first generation reported higher PTG scores relative to the comparison group, with small effect sizes for the overall group differences, η2 P=.029 . These results are discussed in the historical and political context of postwar Czechoslovakia.
Keywords: Česká republika; posttraumatická stresová porucha; Slovakia; posttraumatický růst; Slovenská republika; Holocaust; Humans; přežívající; Czech Republic; Stress Disorders, Post-Traumatic; Child; dítě; lidé; Survivors; Posttraumatic Growth, Psychological; holocaust